Neurodevelopment and Gross Motor Function Outcomes in Children at Risk or Diagnosed with Cerebral Palsy using Snoezelen Multisensory Room - Ali, Ameerah; Yusoff, Surini; Wan Ab. Rahman, Wan Mohd Aiman; Van Rostenberghe, Hans; Yaacob, Najib Majdi; Dinsuhaimi, Fatimah Az-Zahraa’ (Malaysian Journal of Medical Sciences, 2025)
Background: The Snoezelen multisensory room is an internationally recognised intervention designed to provide sensory stimulation that promotes developmental progress in children. This study aimed to evaluate neurodevelopmental and gross motor outcomes in children at risk of, or diagnosed with, cerebral palsy and who received neurodevelopmental therapy in the Snoezelen multisensory room at Hospital Pakar Universiti Sains Malaysia, Kelantan. Methods: Twenty-six patients aged three to 24 months, either at risk of or diagnosed with cerebral palsy, were recruited. However, only 20 patients completed the study. All participants underwent neurodevelopmental therapy in the Snoezelen multisensory room for 12 weeks. Demographic and clinical characteristics were recorded. Neurodevelopment was assessed using the Hammersmith Infant Neurological Examination (HINE), and gross motor function was evaluated using the Gross Motor Function Measure (GMFM-88) scores. Assessments were performed before therapy and after 12 weeks. Pre- and post-therapy scores were compared using paired t-tests. Results: HINE scores increased significantly from pre-therapy (mean = 60.70, standard deviation [SD] = 16.19) to post-therapy (mean = 66.75, SD = 18.18; t = –3.211, P = 0.005). GMFM-88 scores also showed significant improvement from pre-therapy (mean = 49.00, SD = 34.34) to post-therapy (mean = 101.95, SD = 55.70; t = –6.116, P < 0.001). Conclusion: Neurodevelopmental therapy delivered in a Snoezelen multisensory room was associated with significant improvements in neurodevelopmental and gross motor function after 12 weeks among children at risk of cerebral palsy.